Low Levels of Fruit Nitrogen as Drivers for the Evolution of Madagascar's Primate Communities. Issue 1 (December 2017) - Donati, Giuseppe; Santini, Luca; Eppley, Timothy; Arrigo-Nelson, Summer; Balestri, Michela; Boinski, Sue; Bollen, An; Bridgeman, LeAndra; Campera, Marco; Carrai, Valentina; Chalise, Mukesh; Derby Lewis, Abigail; et al.
Abstract The uneven representation of frugivorous mammals and birds across tropical regions – high in the New World, low in Madagascar and intermediate in Africa and Asia – represents a long-standing enigma in ecology. Several hypotheses have been proposed to explain these differences but the ultimate drivers remain unclear. Here, we tested the hypothesis that fruits in Madagascar contain insufficient nitrogen to meet primate metabolic requirements, thus constraining the evolution of frugivory. We performed a global analysis of nitrogen in fruits consumed by primates, as collated from 79 studies. Our results showed that average frugivory among lemur communities was lower compared to New World and Asian-African primate communities. Fruits in Madagascar contain lower average nitrogen than those in the New World and Old World. Nitrogen content in the overall diets of primate species did not differ significantly between major taxonomic radiations. There is no relationship between fruit protein and the degree of frugivory among primates either globally or within regions, with the exception of Madagascar. This suggests that low protein availability in fruits influences current lemur communities to select for protein from other sources, whereas in the New World and Old World other factors are more significant in shaping primate communities.